Interaction of Calf Thymus DNA with the Ni(II) Complex of Sodium 1,4-Dihydroxy-9,10-Anthraquinone-2-Sulphonate: A Novel Method of Analysis Using Cyclic Voltammetry - Partha Sarathi Guin; Piyal Das; Saurabh Das; Parikshit Chandra Mandal (International Journal of Electrochemistry)
Hydroxy-9,10-anthraquinones are cheaper alternatives to anthracycline drugs. They closely resemble anthracycline drugs both from a structural and functional viewpoint. Electrochemical behavior of the Ni(II) complex (Na2[Ni(NaLH)2Cl2]⋅2H2O) of sodium 1,4-dihydroxy-9,10-anthraquinone-2-sulphonate (NaLH2), analogue of the core unit of anthracycline anticancer drugs, was studied at physiological pH using cyclic voltammetry. The Ni(II) complex of sodium 1,4-dihydroxy-9,10-anthraquinone-2-sulphonate undergoes diffusion-controlled one-electron reduction that enables performing an electrochemical study on the interaction of the complex with calf thymus DNA. The complex was titrated with increasing concentrations of DNA, and the reduction peak for the unbound complex helped in evaluating binding parameters. Analysis of binding data using nonlinear curve fit in a cyclic voltammetry experiment is the first such attempt. The paper evaluates site size of interaction that also serves as a means to determine stoichiometry of complex formation, between a metal ion and ligand from a DNA interaction study, probably a first of its kind.